1992
DOI: 10.1002/hep.1840150519
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Hepatic Cholestanol, Squalene and Noncholesterol Sterols in Man: A Study on Liver Transplantation

Abstract: Serum noncholesterol sterols indicate overall cholesterol metabolism in a variety of experimental and clinical conditions. In patients with advanced primary biliary cirrhosis serum cholestanol, a 5 alpha-derivative of cholesterol, is markedly increased, and cholesterol precursors, which are indicators of cholesterol synthesis, are clearly reduced, as is the ratio of plant sterols (campesterol/sitosterol). Therefore these variables were studied in the livers and sera of 23 patients undergoing liver transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 29 publications
4
22
3
Order By: Relevance
“…This relationship was also clear in end-stage PBC, but not as consistent as in ALF, as high serum cholestanol (ratios) indicated low ratios of only lathosterol/bilirubin and campesterol/sitosterol. Accordingly, our results are in accordance with earlier studies among PBC-patients, which showed that hypercholestanolemia and accumulation of cholestanol in tissues develop gradually during worsening state of PBC [10,11,15,16].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This relationship was also clear in end-stage PBC, but not as consistent as in ALF, as high serum cholestanol (ratios) indicated low ratios of only lathosterol/bilirubin and campesterol/sitosterol. Accordingly, our results are in accordance with earlier studies among PBC-patients, which showed that hypercholestanolemia and accumulation of cholestanol in tissues develop gradually during worsening state of PBC [10,11,15,16].…”
Section: Discussionsupporting
confidence: 95%
“…These liver diseases were chosen, because they both represent a cholestatic liver failure, and because serum sterol profiles and cholesterol metabolism of ALF of unknown etiology have not been elucidated so far. In this respect, PBC-patients have been studied most widely [10,11,15,16], and PBC is one of the commonest indications for LTX in Finland; thus, they form a suitable reference group and study population of sufficient size. The following hypotheses were tested: (I) patients with ALF and PBC have differential patterns in their serum sterols and sterol metabolism before and after LTX [10,15], (II) certain profiles of serum sterols are related to poor liver function prior to LTX [15,16], and (III) ALF can be caused by abnormal sterol metabolism [17].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in cholesterol metabolism are not mirrored by routine serum cholesterol and lipoprotein measurements [28] . Moreover, the direct methods available to evaluate cholesterol metabolism are complex and laborious, and require labeling techniques, feces collection, and dietary recalls over several days.…”
Section: Difficulties Of Assessing Cholesterol Metabolism In Cholestasismentioning
confidence: 99%
“…On the other hand, diet-derived plant sterols (e.g., campesterol and sitosterol) and the liversynthesized cholesterol metabolite cholestanol are markers of cholesterol absorption efficiency [30] . These markers have been investigated in PBC before and after LT [15,28,[32][33][34] . Compared to that in healthy controls, intestinal cholesterol absorption is reportedly reduced by 2/3 in cases of prolonged severe intrahepatic cholestasis leading to cirrhosis and end-stage liver failure, as seen in PBC [35] .…”
Section: Difficulties Of Assessing Cholesterol Metabolism In Cholestasismentioning
confidence: 99%
See 1 more Smart Citation